EFFECTS OF HEALTH EDUCATION TO KNOWLEDGE, ATTITUDE AND BREASTFEEDING BEHAVIOR IN BABY - Nurhayati, Ety (Indonesian Journal of Nursing Health Science, 2018)
A good fathers knowledge of breastfeeding will have a significant effect on the role of the father, namely the search for information on breastfeeding and baby food, the involvement in making decisions about current feeding. Health education is an application of the concept of education in the field of health that aims to change understanding in the field of health and can use existing health facilities appropriately and accordingly. This study aims to determine the effect of health education on breastfeeding knowledge and attitudes of husbands about breast milk. This research is a quantitative research with quasi experiment post test only with control group design. The population of this study is a couple (husband and wife) postpartum vaginal mothers who breastfeed in the region of Bekasi. Sample amounted to 66 couples of postpartum mothers taken consecutive sampling. The results of this study indicate that the knowledge and attitudes of respondents increased after health education (p <0.05), but there was no significant difference between infant feeding behavior in control group and intervention after health education (p-Value> 0,05) . The study recommends that subsequent research further develop factors that influence and support infant feeding behavior and optimal breastfeeding utilization by using random sampling techniques so as to better describe the population.Â Keywords : knowledge, attitude, breastfeeding behavior, health education